2021
DOI: 10.1111/jerd.12808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thickness, cement shade, and coffee thermocycling on the optical properties of zirconia reinforced lithium silicate ceramic

Abstract: Objective: To investigate the effect of thickness, cement shade, and coffee thermocycling (CTC) on the optical properties of zirconia reinforced lithium silicate (ZLS) paired with different shades of a resin cement.Materials and Methods: Thirty ZLS specimens were prepared in two different thicknesses (0.8 and 1.5 mm) and three different resin cement shades (Tr, A2, and A3) were applied (n = 5). Color determinations were done before and after 5000 CTC by using a noncontact spectroradiometer. Color change due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…However, new materials that have similarities and differences with LDS are frequently introduced [ 11 , 12 ]. One of those materials was zirconia-reinforced lithium silicate glass-ceramic (ZLS; Vita Suprinity, Vita Zahnfabrick, Bad Säckingen, Germany), which was launched as a unique material that combines the advantages of lithium disilicate and zirconia [ 13 , 14 ] due to 10 wt% of zirconium dioxide dissolved in its glassy matrix [ 15 ]. Recently, a new lithium disilicate called nano-lithium disilicate glass-ceramic (NLD; Amber Mill, Hass, Gangneung, Korea) has been marketed [ 7 , 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, new materials that have similarities and differences with LDS are frequently introduced [ 11 , 12 ]. One of those materials was zirconia-reinforced lithium silicate glass-ceramic (ZLS; Vita Suprinity, Vita Zahnfabrick, Bad Säckingen, Germany), which was launched as a unique material that combines the advantages of lithium disilicate and zirconia [ 13 , 14 ] due to 10 wt% of zirconium dioxide dissolved in its glassy matrix [ 15 ]. Recently, a new lithium disilicate called nano-lithium disilicate glass-ceramic (NLD; Amber Mill, Hass, Gangneung, Korea) has been marketed [ 7 , 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Zirconia-reinforced lithium silicate glass ceramic (ZLS) has been launched as a unique material that combines the advantages of lithium disilicate and zirconia [12][13][14][15][16] due to 10 wt% of zirconium dissolved in its glassy matrix. 17 Currently, ZLS is available either in crystallized (Celtra Duo; Dentsply Sirona) or pre-crystallized form (Vita Suprinity; Vita Zahnfabrik). 18,19 Even though both materials comprise a similar microstructure, 18,20 a previous study has reported that precrystallized ZLS had higher flexural strength values than crystallized ZLS.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods can be used to measure the color change, whereas a spectrophotometer is considered a reliable, reproducible, and accurate color measuring device so it was used in this study. 7,9,19,32 Color change of specimens was measured against a white background as it compensates for chromatic shortage resulting from potential absorption effects on any of the color parameters. 39,40 Results of this study showed that coffee immersion produced the highest color change in Vita Enamic followed by Lava Ultimate where both values were greater than the acceptable threshold (AT) ≤3.3 for color change 3,7,19,26,29,32,41 while Vita Suprinity recorded the least color change.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Computer-aided design/computeraided manufacturing (CAD/CAM) monolithic block materials opened up a new horizon in dental treatment to meet the expectations of the clinicians and patients allowing time-efficient fabrication of precise tooth-colored highly reliable restorations. [1][2][3][4][5][6][7][8][9][10] Generally, CAD/CAM materials used to produce monolithic restorations can be categorized as ceramic/glass ceramic, indirect resin-based composite, and hybrid ceramic. Ceramic/glass ceramic include zirconia, lithium disilicate ceramics, zirconia reinforced lithium silicate ceramics, leucite reinforced ceramics and feldspathic ceramics.…”
Section: Introductionmentioning
confidence: 99%